Rancang Bangun Aplikasi Tele-Kendali Komputer Via Jaringan PSTN dengan Modul DTMF dan Mikrokontroller Attiny2313 - Yuliardi Erdani; Hendy Rudiansyah (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
Extremely long distance control, hardly reachable actuator/target and costly network development  are some concerns within a distance control system. Such control is computer control for advertisements placed in tricky areas as locations over the bridge, at a junction, etc. The provider usually performs system inactivation in order to save energy. But until now, it is still difficult to find a system that can be turned on and off in remote manner. That is why the distant control using telephone can be the best alternative solution. Not only can the telephone be used in wide range of area, but also easily operated. The developed circuit in this research uses dual tone multiple frequency (DTMF). It is operated by pressing telephone button as control input for microcontroller. The microcontroller processes the input and controls the computer via relay and serial port. The result of experiment shows that the developed application is able to shut down and turn on computer as well as to apply software remotely.